Response to Wilson: Forget Multiple Tools; Use Mathematica - Issaevitch, T. (IEEE computational science & engineering, 1996)
In the Summer 1996 issue of IEEE CS&E, the original article by Wilson and the reply by McConnel propose two quite different curricula. The first focuses on the various tasks an engineer must perform, and the second on more fundamental aspects of software engineering. Both are important to teach and both authors make good cases. Rather than add to this discussion, the present report focuses on the medium (language) in which these subjects and principles should be taught. With a proper choice of language, both curricular goals can be achieved.